e-Research Collaboration Theory, Techniques and Challenges - Anandarajan, Murugan.; Anandarajan, Murugan. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
Research in both academic and non-academic circles has remained virtually identical in its conduct and organization over the last few decades. Disparate groups of researchers have worked on their ideas, projects and inventions in isolated clusters, with little sharing of information and synergies from collaboration. The advent of social networks and Web portals such as MyNetResearch have led to the creation of new research networks that dramatically reduces the barriers and obstacles to collaboration by researchers who are geographically, organizationally and disciplinarily distant. The current tens of thousands and eventually millions of researchers who will use research networks are ushering in a new paradigm for research. In this paradigm collaboration is made much easier, sharing of research knowledge is instant, and synergies from routine collaboration will yield huge advances in research productivity and innovation. This book examines how research networks are changing the practice of research and decide how best to embrace such technologies and use them to their best advantage.